Pelatihan E-Filing Aplikasi Arsip Digital bagi Guru-guru SMK - puspasari, durinta; Nugraha, Jaka; Pahlevi, Triesninda; Wulandari, Siti (Abimanyu : Jornal of Community Engagement, 2022)
The use of information and communication technology has become an effective and efficient way of conveying information, especially in storing various information using electronic archives or what is called e-filing of digital archive applications. For teachers, the need for the ability to use e-filing digital archive applications is felt to facilitate the process of storing various kinds of incoming and outgoing letters. Considering that there are so many documents that need to be archived, if the documents can be archived electronically it will be easier. The method used in this Community Service activity is training through several stages of program socialization and the introduction and implementation of the strategies used are lectures and practice. The implementation of community service activities carried out by the Community Service team has received a positive response from Vocational High School teachers. This can be seen based on the questionnaire responses and testimonials given by the teachers participating in the e-filing training for digital archive applications at the Tunas Wijaya Vocational High School Surabaya. So that this training activity was responded positively by the training participants because the training participants were very enthusiastic to follow this activity until it was completed, and the trainees wished to be able to apply it in learning activities, and requested that this Community Service activity be sustainable.